(Invited) Materials and Processes for Superconducting Qubits and Superconducting Electronic Circuits on 300mm Wafers. (9th April 2018) - Papa Rao, Satyavolu S.; Hobbs, Christopher; Olson, Stephen; Foroozani, Neda; Chong, Hyuncher; Stamper, Harlan; Martinick, Brian; Ashworth, Dominic; Bunday, Benjamin; Malloy, Matthew; Holland, Eric; Nalaskowski, Jakub; et al.
Abstract : The promise of quantum computing for solving problems of interest to society (e.g., drug design, cryptography, etc) can be advanced by the fabrication of high performance qubits that faithfully replicate the designer's intent. 3D integrated superconducting digital electronics are being considered for energy-efficient, low-latency qubit control, and for readout. The development of 'manufacturing-friendly' qubit architectures is essential for building repeatable, well-controlled qubits into quantum computing systems equipped with 3D integrated qubit control and communication. In this paper, the potential advantages and challenges of qubit and superconducting electronics fabrication using advanced 300mm wafer processes will be discussed, with reference to millikelvin characterization results from qubits fabricated using 193nm lithographic techniques on 300mm wafers. Fabrication of high quality interfaces will be discussed, with high resolution TEM and other analyses guiding such process development, serving to illustrate the potential for further increases in qubit performance through the use of 300mm fabrication.